Inhibition of vasopressin release in man by an opiate peptide. - Grossman, A; Besser, G; Milles, J; Baylis, P (1980)
The opiate control of vasopressin secretion in man was investigated with a long-acting analogue of met-enkephalin, DAMME (FK33-824, Sandoz). Infusion of 1 mg DAMME into water-deprived volunteers produced a diuresis which was attenuated by naloxone; there was no change in water excretion when subjects were hydrated. Plasma-immunoreactive-vasopressin failed to rise after DAMME administration, despite osmotic stimulation with hypertonic saline infusion. Opiates appear to be involved in mechanisms which suppress the osmotically mediated release of vasopressin, while opiate involvement in baroceptor-mediated release may be quite different.